Genome-Wide Identification and Characterization of the bHLH Transcription Factor Family in Pepper (Capsicum annuum L.) - Zhang, Zhishuo; Chen, Juan; Liang, Chengliang; Liu, Feng; Hou, Xilin; Zou, Xuexiao (Frontiers in Genetics, 2020)
Plant basic/helix–loop–helix (bHLH) transcription factors are involved in the regulation of various biological processes in plant growth, development, and stress responses. However, members of this important transcription factor family have not been systematically identified and analyzed in the important vegetable crop, pepper (Capsicum annuum L.). In this study, we identified 122 CabHLH genes in the pepper genome and renamed them based on their chromosomal locations. CabHLHs were divided into 21 subfamilies based on their phylogenetic relationships, and genes from the same subfamily had similar motif compositions and gene structures. Sixteen pairs of tandem and segmental duplicated genes were detected in the CabHLH family. All of the duplicated gene pairs had Ka/Ks values of less than one and had been subjected to purifying selection pressure during evolution. The gene ontology, cis-elements and expression patterns analysis of CabHLHs revealed that they may be involved in plant development and stress responses. This study is the first comprehensive analysis of CabHLH gene family and will serve as a reference for further characterization of their molecular functions.